Islamic awakening and its role in Islamic solidarity in Egypt - Abd.Rahman, Saodah Binti; Nurullah, Abu Sadat (Journal of Islam in Asia (E-ISSN 2289-8077), 2010)
Islamic revivalism led to the development of Islamic awakening throughout the Muslim world by uniting the Muslim society. In the process of liberating the Muslim countries from the colonists, all Muslims felt the necessity of unity, including the traditionalists and secularists. Historically, Islamic awakening brought about the spirit of establishing principles of Islam in all affairs of the country, including the establishment of Islamic state and implementation of Islamic laws. In the case of Egypt, the Islamic awakening resulted in the emergence of three distinct Muslim groups, namely – moderate Muslims, secularists, and radicals. This paper concentrates on the moderate Muslims, because in our view they are able to successfully incorporate Islamic principles at the grassroot level. The Islamic organization which is established by the moderate Muslims are actively involved in social services and charity activities, such as al-IkhwÉn al-MuslimËn (the Muslim Brotherhood). This movement is also very successful in establishing economic prosperity, such as the investment company called al-RayyÉn. The Islamic awakening in Malaysia brought about the consciousness of adopting and practicing the Islamic way of life. The process of implementing the principles of Islam was based on a gradual evolutionary process, rather than drastic method. Therefore, the implementation of Islamic law is carried out smoothly, and it is accepted by the Muslims and non-Muslims alike. For that reason, various institutions have been established, such as, Islamic universities, Islamic banking and insurance, and other Islamic organizations and institutions.